Dignity of elderly adults from the perspective of nurses: a qualitative descriptive study - Šárka Šaňáková; Juraj Čáp (University of Ostrava, 2018)
Aim: The aim of these descriptive qualitative study was to analyze dignity in nursing care in institutionalised elderly adults from the perspective of nurses, and to identify factors affecting dignity. Design: A descriptive qualitative study. Methods: A descriptive qualitative study employing individual in-depth interviews. The sample comprised ten general nurses working in health and social institutions with round-the-clock care for elderly adults. A thematic analysis was used to analyze the data. Results: Six main themes have been identified in relation to dignity: Regarding elderly adults as unique human beings; Privacy and embarrassment; Quality of relationships; Communication; Quality of care; and Environment. The main themes were further broken down into 24 sub-themes and their mutual relationships. Among important determinants for dignity, nurses listed sufficient staff and funding, the necessity for health and social workers to cooperate, and family relationships. Conclusion: The resulting schema represents a description of nurses' experience of respecting dignity in primary nursing care for elderly adults. Nurses see dignity in open communication, room for privacy, securing quality individualised care, and preserving current family relationships. The schema may be used for a self-reflection by nurses in direct care for elderly adult, by the management of healthcare institutions and social care, and for students of nursing.are.